2018
DOI: 10.3390/ijms19123944
|View full text |Cite
|
Sign up to set email alerts
|

MiR-19a Overexpression in FTC-133 Cell Line Induces a More De-Differentiated and Aggressive Phenotype

Abstract: In recent years, microRNAs (miRNAs) have received increasing attention for their important role in tumor initiation and progression. MiRNAs are a class of endogenous small non-coding RNAs that negatively regulate the expression of several oncogenes or tumor suppressor genes. MiR-19a, a component of the oncogenic miR-17-92 cluster, has been reported to be highly expressed only in anaplastic thyroid cancer, the most undifferentiated, aggressive and lethal form of thyroid neoplasia. In this work, we evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…By regulating target genes of various signalling pathways including gene expression of known oncogenes and tumour suppressor genes, they play a crucial role for cell differentiation, migration, invasion and even epithelial-to-mesenchymal transition (EMT) [26][27][28]. Furthermore, different and distinct miRNA profiles were identified in different TC subtypes [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…By regulating target genes of various signalling pathways including gene expression of known oncogenes and tumour suppressor genes, they play a crucial role for cell differentiation, migration, invasion and even epithelial-to-mesenchymal transition (EMT) [26][27][28]. Furthermore, different and distinct miRNA profiles were identified in different TC subtypes [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…36 Our group recently demonstrated that miR-19a overexpression in FTC-133 cell line induces a more de-differentiated and aggressive phenotype. 37 In this study, we aim to confirm the role of mir-19a overexpression in thyroid cancer progression and malignancy by using another welldifferentiated cell line, PTC, showing a miR-19a expression level lower than FTC. In addition, to further support the mir-19a function in promoting tumor progression, we evaluated the effect of its inhibition in ATC cell line, which expresses higher basal level than PTC and FTC.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors also include the possibility of overexpression of microRNAs, which suggests a possible involvement in the differentiation and malignancy [10,11].…”
Section: Introductionmentioning
confidence: 99%